INCREASING THE LEARNING ACTIVITY OF PRIMARY SCHOOL STUDENTS BY ORGANIZING MUSICAL AND RHYTHMIC ACTIVITIES BASED ON INNOVATIVE APPROACHES IN THE NEW DEVELOPMENT STRATEGY (Web of Teachers: Inderscience Research, 2026)
One of the areas where the New Uzbekistan Development Strategy is yielding practical results is the education system. Today's progress aims to bring about updates in all areas, advanced technological approaches, and most importantly, the formation of a sense of striving for progress in the minds of the younger generation. In this regard, strengthening their motivation to learn, activity and creativity, and comprehensively implementing life-oriented programs have become one of the priority tasks of state policy. The new development strategy is aimed at improving music and rhythmic-cultural activities at all levels of modern education, especially in primary grades, based on innovative approaches, which is also important in increasing children's educational activity.